1998
DOI: 10.1021/bi9806908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen Bonds on the Redox Potential and Electronic Structure of the Bacterial Primary Electron Donor

Abstract: The primary donor, P, of photosynthetic bacterial reaction centers (RCs) is a dimer of excitonically interacting bacteriochlorophyll (BChl) molecules. The two constituents are named PL and PM to designate their close association with the L- and M-subunits, respectively, of the RC protein. A series of site-directed mutants of RCs from Rhodobacter sphaeroides has been constructed in order to model the effects of hydrogen bonding on the redox midpoint potential and electronic structure of P. The leucine residue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
97
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 35 publications
(76 reference statements)
3
97
0
Order By: Relevance
“…Tyrosine and histidine both donate hydrogen bonds of similar strength to P; yet, the effect of tyrosine on E m is much weaker. Histidine side chains, however, have a strong dipole moment and thus may raise E m by charge-dipole interaction (38,42). The increased polarity in the environment of the cofactor is also expected to lead to an increase of , as seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine and histidine both donate hydrogen bonds of similar strength to P; yet, the effect of tyrosine on E m is much weaker. Histidine side chains, however, have a strong dipole moment and thus may raise E m by charge-dipole interaction (38,42). The increased polarity in the environment of the cofactor is also expected to lead to an increase of , as seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Stark effect spectroscopy (35), photochemically induced dynamic nuclear polarization (photo-CIDNP), 13 C solid-state NMR (36), EPR, ENDOR (electron-nuclear double resonance), and TRIPLE (electron-nuclear-nuclear triple resonance) studies (37,38) all have shown asymmetric electron distributions in the ground, excited, and ionized states of the special pair in wild-type RCs, and addition or removal of hydrogen bonds between the special pair and the protein matrix affects the spin distribution between the P L and P M BChl monomers (37).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the acetyl group, hydrogen bonding to neighboring residues modulate the functional properties, specifically the excitation energies of BChl a in light harvesting (LH) complexes from purple bacteria (3,4). It has also been suggested that hydrogen bonding to the acetyl group contributes to the tuning of the redox energies of P870 in bacterial reaction centers (5), but this is still under some dispute (6). Hydrogen bonding to the C13 1 keto carbonyl at the isocyclic ring, which is common to all chlorophylls, seems to be widespread (6 -9) but appears to have less or no effect on the electronic properties of (B)Chl (6,9,10).…”
mentioning
confidence: 99%
“…The carbonyl groups frequently interact with the surrounding polypeptide and/or neighboring pigments. In particular, the H-bonding state of the acetyl carbonyl of BChls has been recognized to modulate the spectral and, although still disputed, redox properties of these molecules (10). H-bonding to the C- 13 1 keto carbonyl at the isocyclic ring, which is common to all bacteriochlorophylls and chlorophylls, seems to be widespread (see e.g.…”
mentioning
confidence: 99%